Prescrição e efetividade: análise das Ações Penais de competência da Vara de Violência Doméstica e Familiar Contra a Mulher de São Luís (2014-2018) - MAIA, Maicy Milhomem Moscoso (2020)
Ensuring the reasonable duration of the process has been one of the greatest challenges for the Brazilian judiciary. This research turns to the analysis of the time of the process in the area of the domestic violence against the women, from the collection and analysis of the data of the sentences handed down in criminal action by the only court with such competence of the city of São Luís/MA. Violence against women is understood to mean gender-based actions or omissions that cause death, harm, physical, sexual or mental suffering in both public and private circles. It is a true violation of human rights, fundamental freedoms, and ultimately against the principle of the dignity of the human person. In Brazil, this kind of violence is often disguised and perpetrated in various social sectors, due to a naturalization process of this type of aggression, which is materialized in the most brutal acts, such as crimes against life, against sexual dignity and freedom. as well as offenses against the psychic, emotional, moral, patrimonial tranquility of women. To specifically combat violence against women in the family and at home, Law nº. 11.340/2006, popularly known as the “Maria da Penha Law”, responsible for creating mechanisms to curb and prevent domestic and family violence against women. However, after more than 10 (ten) years have passed since its publication, there are still doubts about the effectiveness of this Law, especially when questioning the efficiency of the jurisdictional units with jurisdiction for its application and the time taken to prosecute of this nature. In this sense, we seek to understand the growing demand for crimes committed under the auspices of domestic violence under the term of duration for the prosecution of criminal actions of this nature and the effectiveness of judicial action. It investigates the application of the Maria da Penha Law and whether the judiciary has complied with the precepts of prevention, eradication and punishment of domestic and family violence against women. This paper argues that part of the growth of this demand is related to the inefficiency of the time management of proceedings by the studied court, a circumstance that facilitates the pathological incidence of criminal prescription. This factor fits the concept of institutional violence not only against victims of domestic violence, but also to society as a whole.